Comparison between full face and hemifacial CBCT cephalograms in clinically symmetrical patients: a pilot study - Cintia Helena Zingaretti Junqueira; Guilherme Janson; Marisa Helena Zingaretti Junqueira; Lucas Marzullo Mendes; Eduardo Esberard Favilla; Daniela Gamba Garib (Dental Press Editora, 2015)
INTRODUCTION: One of the advantages of cone-beam computed tomography (CBCT) is the possibility of obtaining images of conventional lateral cephalograms derived from partial or complete reconstruction of facial images. OBJECTIVE: This study aimed at comparing full face, right and left hemifacial CBCT cephalograms of orthodontic patients without clinical facial asymmetry. METHODS: The sample comprised nine clinically symmetrical patients who had pretreament full face CBCT. The CBCTs were reconstructed so as to obtain full face, right and left hemifacial cephalograms. Two observers, at two different times, obtained linear and angular measurements for the images using Dolphin 3D software. Dependent and independent t-tests were used to assess the reproducibility of measurements. Analysis of Variance and Kruskal-Wallis tests were used to compare the variables obtained in the CBCT derived cephalometric views. RESULTS: There was good reproducibility for CBCT scans and no statistically significant differences between measurements of full face, right and left hemifacial CBCT scans. CONCLUSIONS: Cephalometric measurements in full face, right and left hemifacial CBCT scans in clinically symmetrical patients are similar.